A Pythagorean triple is an ordered triplet [ x , y , z ] of positive integers satisfying the equation x 2 + y 2 = z 2 .
Consider a Pythagorean triple [ a , b , c ] such that:
a is a power of two.
b is one less than a power two.
c is one more than the same power of two as b .
If you multiply a by 8 you will get a number which is one less than c .
What is the sum a + b + c ?
Mind that a number which is a power of two is for example 1 6 because 1 6 = 2 4 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That is awkwardly easier than I thought. Nice!
Let the integers of the triplet be x 2 − y 2 , 2 x y , x 2 + y 2 . Let 2 x y = 2 n ⟹ x y = 2 n − 1 , x 2 − y 2 = 2 p − 1 , x 2 + y 2 = 2 p + 1 . Then x = 2 p / 2 , y = 1 . Therefore p = 2 ( n − 1 ) . Also, 8 × 2 x y = 2 p ⟹ 2 n + 3 = 2 2 ( n − 1 ) ⟹ n = 5 . Therefore a = 2 x y = 2 5 = 3 2 , b = 2 8 − 1 = 2 5 5 , c = 2 8 + 1 = 2 5 7 and a + b + c = 3 2 + 2 5 5 + 2 5 7 = 5 4 4 .
By using the first and the last point, we get two equations.
a 2 + b 2 = c 2
8 a = c − 1
Now let's use the remaining points and let
a = 2 α
b = 2 β − 1
c = 2 β + 1
for some integers α , β ∈ N .
By substituting for a , b , c , we get
a 2 + b 2 = c 2
( 2 α ) 2 + ( 2 β − 1 ) 2 = ( 2 β + 1 ) 2
Mind that a m ⋅ a n = a m + n and ( a m ) n = a m ⋅ n .
2 2 α + 2 2 β − 2 ⋅ 2 β + 1 = 2 2 β + 2 ⋅ 2 β + 1
2 2 α = 4 ⋅ 2 β
2 2 α = 2 2 ⋅ 2 β
2 2 α = 2 2 + β .
By eliminating the basis:
2 α = 2 + β .
Now substitute a , b , c into the second equation.
8 a = c − 1
8 ⋅ 2 α = ( 2 β + 1 ) − 1
2 3 ⋅ 2 α = 2 β
2 3 + α = 2 β
3 + α = β .
We have obtained a system of two equations with two variables which we can solve easily.
(I) 2 α = 2 + β
(II) 3 + α = β
(I) − (II) :
2 α − α − 3 = 2 + β − β
α − 3 = 2
α = 5
By substitution into (II) :
3 + 5 = β
β = 8 .
Finally, we just subtitute α , β back into a , b , c and sum them up.
a = 2 α = 2 5 = 3 2
b = 2 β − 1 = 2 8 − 1 = 2 5 5
c = 2 β + 1 = 2 8 + 1 = 2 5 7
a + b + c = 3 2 + 2 5 5 + 2 5 7 = 5 4 4
We can confirm that 3 2 2 + 2 5 5 2 = 2 5 7 2 .
Oh, I see now that the substitution was unnecessary. 🙃
Let x = largest ( 1 more than a square)
x - 2 = middle ( 1 less than a square)
(x-1)/8 = smallest
x^2 =(x-2)^2+((x-1)/8)^2
x^2=x^2-4x+4+(x^2-2x+1)/64
64x^2=64x^2-256x+256+x^2-2x+1
0=x^2-258x+257
0= (x-257)*(x-1)
x=257 or x=1(not 1 more than square)
x-2=255
(x-1)/8=32
Sum = 544
x = 1 is definitely one more than a square, but x − 2 is not positive. Hence you can discard this value.
Problem Loading...
Note Loading...
Set Loading...
Since a is a power of 2 and 8 is also a power of 2 , 8 a is also a power of 2 and ⟹ b = 8 a − 1 and c = 8 a + 1 . Since c is the largest, we have:
a 2 + b 2 a 2 + ( 8 a − 1 ) 2 a 2 + 6 4 a 2 − 1 6 a + 1 a 2 ⟹ a = c 2 = ( 8 a + 1 ) 2 = 6 4 a 2 + 1 6 a + 1 = 3 2 a = 3 2 a power of 2
Therefore a + b + c = 3 2 + 8 × 3 2 − 1 + 8 × 3 2 + 1 = 1 7 × 3 2 = 5 4 4 .